Alternatives for automatic rendering of Brazil and other geographic regions’ territory thematic cartograms - Nascimento, Luiz; Reznik, Regina; Pinheiro, Tarsus; Esperança, Claudio; Farias, Ricardo (InfoDesign, 2025)
This article presents alternative concepts for rendering thematic cartograms, using primitive shapes arranged under different concepts of spatial distribution, aiming to meet the criteria explained in the proposal in a more intuitive way. initially defended by Barreto, Kosminsky, and Esperança(2018). Graphic rendering algorithms, developed for the automatic generation of thematic cartograms according to the concepts presented here, and following the methodology of Speckmann and Verbeek (2010)’s work, are also presented.